2017
DOI: 10.1080/11250003.2016.1274436
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of introduced brook troutSalvelinus fontinalis(Salmonidae) within alpine lakes: evidences from a fish eradication campaign

Abstract: Brook trout Salvelinus fontinalis have been used worldwide to stock fishless alpine lakes, negatively affecting native biota. Understanding its spatial ecology in invaded ecosystems can provide information to interpret and contrast its ecological impact. We opportunistically used capture points of brook trout gillnetted during an eradication campaign to assess the distribution patterns of four unexploited populations inhabiting high-altitude lakes. The main eradication method implies the use of many gillnets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…The capture efficiency analysis conducted during the two campaigns confirmed this observation and showed achieved total capture rates of over 99% for 0+ and 100% for adult trout. These results were in accordance with Knapp andMatthews (1998), andTiberti et al (2017), hypothesising that the eradications can be considered concluded after 1 year without fish capture. Overall, the electrofishing method of fish capture and removal was shown to be generally applicable to headstreams in Mediterranean climatic zones prone to summer droughts, only if matched to the use of the electric barrier.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The capture efficiency analysis conducted during the two campaigns confirmed this observation and showed achieved total capture rates of over 99% for 0+ and 100% for adult trout. These results were in accordance with Knapp andMatthews (1998), andTiberti et al (2017), hypothesising that the eradications can be considered concluded after 1 year without fish capture. Overall, the electrofishing method of fish capture and removal was shown to be generally applicable to headstreams in Mediterranean climatic zones prone to summer droughts, only if matched to the use of the electric barrier.…”
Section: Discussionsupporting
confidence: 80%
“…Chemical methods include the use of the piscicides antimycin, rotenone or ozone, and have mainly been used to eradicate exotic fish populations, or fish which may spread disease, in order to protect threatened or endangered species (Gresswell 1991;Demong 2001;Allen et al 2006;Buley et al 2017). Mechanical methods include the use of gill netting (Knapp & Matthews 1998;Tiberti et al 2017), and repeated electrofishing (Kulp & Moore 2000;Carmona-Catot et al 2010;. The use of chemical methods for eradication is often controversial due to harmful effects on nontarget species, and lethal effects on aquatic invertebrates and the larval forms of amphibians (Mangum & Madrigal 1999;Ling 2003;Buley et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The capture efficiency was dictated by the ability of the smaller mesh size to entangle the fish. These observations are shared by Tiberti et al [31] who showed that gillnets with a mesh size from 10 to 25 mm entangled brook trout of different size in four high-altitude lakes in the Italian Alps. By contrast, larger mesh sizes (35, 43, 55 mm) were too large to efficiently capture the relatively small brook trout in Balma Lake.…”
Section: Discussionmentioning
confidence: 57%
“…Fish densities were similar and remarkably high both in Lake Dres and in the stream sections (Waters, 1977;Tiberti et al, 2017b). The fact that the recovery of lake dwelling macroinvertebrates started well before the capture of the last fish suggests that fish impact is density dependent.…”
Section: Fish Densitymentioning
confidence: 90%